Hydroponic cultivation of lettuce (Lactuca sativa) using laboratory wastes from nitrogen, phosphorus, and potassium analyses of the Regional Soils Laboratory, Department of Agriculture Regional field Office 6 - Bullo, Jean G (University of the Philippines in the Visayas, 2019)
The study was conducted to evaluate the nutrient absorption, dry matter content, and growth of lettuce (Lactuca sativa) using formulated nutrient solution from laboratory wastes generated grom Regional Soils Laboratory, Region 6. The hydrophonic system consists of six treatments : Nitrogen analysis waste solution (T1), Phosphorus analysis waste solution (T2), Potassium analysis waste solution (T3), Combined N, P. K wastes (T4), Tap water (T5), and Commercial hydrophonic solution (T6). The laboratory wastes were characterized, formulated, and utilized in the hydrophonic system to supply the nutrients needed by plants. Measurements of lenght and width of leaves, length of roots, and dry matter content were submitted to ANOVA and significant interactions sing Tukey's test (p<0.05%). Statistical analysis shows that T2, T3, and T4 have significant differences to T5 and T6 in terms of length and width of leaves, length of roots, and dry matter content. The study showed that the quality of formulated nutrient solution which is associated with electrical conductivity has a crucial effect on the growth and nutrient absorption of the lettuce plants. Plants also exhibit toxicity symptons 7 days after transplanting but eventually recovered its vigor on succeeding weeks. Based on the result of the experiment, it is recommended to assess the micronutrient content of laboratory wastes to minimize possible toxicities and determine the inhibition that take place on plants during the nutrient absorption process.